2017 4th International Conference on Electric Power Equipment - Switching Technology (ICEPE-ST) 2017
DOI: 10.1109/icepe-st.2017.8188830
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the influence of vent aperture size and distribution on arc motion and interruption in low-voltage switching devices

Abstract: Abstract-Enhanced switching performance during the interruption process is achieved when the arc quickly enters and stays within the splitter plate region with the arc itself remaining attached to the surface of the plates. It is well known that the vent design in low-voltage switching devices (LVSDs) has a significant influence on arc motion during an interruption event: however, there has been limited experimental studies correlating arc motion in the whole quenching chamber, including splitter plates region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The magnetic conductance plates and magnetic connections are made of steel with a permeability of • -6000 N m . 2 In the model, there is a circular air outlet whose diameter is 20 mm on both sides of the arc runner [36,37]. Figure 1(b) is a simplified model of the middle cross-sectional view of the arc chamber, and the splitter plates and arc runner are made of copper.…”
Section: Geometric Modelmentioning
confidence: 99%
“…The magnetic conductance plates and magnetic connections are made of steel with a permeability of • -6000 N m . 2 In the model, there is a circular air outlet whose diameter is 20 mm on both sides of the arc runner [36,37]. Figure 1(b) is a simplified model of the middle cross-sectional view of the arc chamber, and the splitter plates and arc runner are made of copper.…”
Section: Geometric Modelmentioning
confidence: 99%
“…Similarly, Yu et al observed the arc velocity is enhanced by increasing the vent size and chamber width in the simplified quenching chamber [7]. Shin et al carried out an experimental study on the influence of vent aperture size and distribution on arc motion and interruption performance in LVSDs [8]. They concluded that the arc moves further and more quickly where the vents are larger.…”
Section: Introductionmentioning
confidence: 97%
“…Previous empirical investigations have been carried out to study arc motion and its influence on current limitation [3] - [8], re-ignition in an attempt to improve the switching performance [2], [9], [10], or arc splitting process by the splitter plates in the quenching chamber of the LVSD [11]. McBride et al investigated the influence of several parameters on arc motion (the duration the arc root remains in the contact region) in miniature circuit breakers (MCBs) by recording arc motion through the arc imaging system (AIS) [3] - [5].…”
Section: Introductionmentioning
confidence: 99%
“…The vent aperture plays an important role on the arc motion and splitter plates lead to increase the voltage drop. The study from Shin et al [3] is devoted to the influence of vent aperture size and repartition on arc motion by arc imaging acquisitions. It is shown that the arc moves further and more quickly in case of larger area of vent opening in the quenching chamber.…”
Section: Introductionmentioning
confidence: 99%